Preventing and treatment of post-dural Puncture Headache - Gawrych, Szymon; Białkowska, Aleksandra; Budziejko, Blanka; Cywińska, Oliwia; Dziarkowski, Dariusz; Kurtyka, Daria; Różański, Gracjan; Dobosiewicz, Anna Maria; Badiuk, Nataliia (Journal of Education, Health and Sport, 2018)
Post-dural Puncture Head (PDPH) is a common undesired side effect of lumbar puncture (LP). It is connected with the leakage of Cerebrospinal Fluid (CSF) at the puncture site outside of spinal cord – in to the dura mater. The intracranial pressure sensitive structures in the brain react with the lowered intracranial pressure triggering pain and other PDPH-related symptoms. Conservative PDPH-preventing therapy includes prolonged bed rest and increased fluids intake – those guidelines were invented as long ago as LP itself and even though modern day research show no connection between following those guidelines and PDPH occurrence yet it is still performed in medical practice. Research shows that crucial for the likelihood of PDPH occurrence is the type of used needle gauge whether it is traumatic or atraumatic and the needle size (its’ diameter). As for the treatment of prolonged PDPH the most beneficial from the pharmacotherapy is the usage of caffeine (used in treatment of different-based headaches as well) combined with other pain-easing medicines. As for the more invasive method of treatment epidural patch is being used. It works as a patch, made of patients’ blood that covers the hole in the dura mater preventing more CSF from leaking outside. It is the most efficient way of treating PDPH.